Right-Wing Authoritarianism and Antipathy Toward Immigrants and Sexual Minorities in the Early Days of the Coronavirus Pandemic in Italy - Pacilli, Maria Giuseppina; Pagliaro, Stefano; Bochicchio, Vincenzo; Scandurra, Cristiano; Jost, John T. (Frontiers in Political Science, 2022)
Theory and research in social, evolutionary, and political psychology indicates that subjective feelings of threat and exposure to objectively threatening circumstances—including pandemic diseases—may contribute to increased affinities for political conservatism, right-wing authoritarianism, and prejudice against out-group members. We investigated these possibilities in the context of Italy, which was the first Western country to be severely affected by the spread of COVID-19. Early on in the pandemic, from March 3–8, 2020, we surveyed 757 Italian adults ranging in age from 18 to 78 years. Results revealed that antipathy toward immigrants and sexual minorities was predicted by (male) sex, COVID-19 anxiety, RWA, and political distrust. Furthermore, COVID-19 anxiety magnified the effect of RWA on disliking of immigrants and sexual minorities (but not obese or disabled people). Contrary to prediction, political trust failed to attenuate the effects of COVID-19 anxiety or RWA on out-group antipathy. Implications for the theories of right-wing authoritarianism and political ideology as motivated social cognition, as well as the state of contemporary Italian politics are discussed.